Agapay Residences redefining a PWD Filipino family home through an assistance-generative residential complex - Antonio, Angelika Emille D. (College of Architecture, University of the Philippines Diliman, 2025)
Persons With Disabilities (PWDs) struggle in assimilating into society due to their disabilities often excluding them from participating in communal activities. A major factor of this is the lack of accessibility, and in turn makes PWDs rely on family members for a majority of their needs. The reliance on their family members also withholds them from achieving independence and living on their own. this project aims to address this problem by creating a space that is fit for PWDs to exercise their own independence by creating accessible facilities while giving them ample living space. The living spaces are designed with adequate room space for ease of access and mobility. There are facilities that encourage PWDs to interact with other PWDs and families that will live within the site. This also gives them a chance to create a community with other PWDs and gain a support system outside of their family and caretakers. The end goal is for PWDs to gain more independence and be able to live a more fulfilling life by giving them space to explore themselves more freely.